EFFECTS OF TEMPERATURE ON THE GROWTH AND SURVIVAL OF MERETRIX MERETRIX JUVENILES IN LABORATORY - Thanh, Nguyen Xuan (Vietnam Journal of Marine Science and Technology, 2014)
This study was conducted to evaluate the effect of temperature on the growth and survival of Meretrix meretrix juveniles. The experiment was conducted with three treatments (150C, 270C and 350C) and three replications was run per each treatment. The results showed that, Meretrix meretrix juveniles grow was the fastest and the highest survival rate (92%) at sea water temperatures were 270C, at lower and upper temperature (150C and 350C) clams grow slowly and survival rate was lower (66% and 45.33% respectively) after one month of culture in laboratory conditions. Our findings contribute information for the appropriate culture techniques and farming management of clams for each production season. Especially, in the farming areas of the Northern is subjected to lasting low temperatures in winter owing to strong cold weather, as well as the effect of persistent high temperature in summer.